Pelatihan Implementasi Deep Learning dalam Rangka Menciptakan Pembelajaran Mendalam dan Bermakna pada Guru Ekonomi SMA/MA Kota Tasikmalaya - Lu'luil Maxnun; Ati Sadiah; Rendra Gumilar; Astri Srigustini; Kurniawan; Dita Amelia Putri; Ai Nur Solihat; Raden Roro Suci Nurdianti; Iis Aisyah (Masyarakat Mandiri : Jurnal Pengabdian dan Pembangunan Lokal, 2026)
The policy to implement the deep learning approach in Indonesian schools starting from the 2025/2026 academic year requires teachers to be well prepared to design and conduct meaningful and in-depth learning. This community service program aimed to enhance the understanding and pedagogical competence of senior high school and madrasah economics teachers in Tasikmalaya City in implementing the deep learning approach comprehensively. The program employed a community-based science and technology application scheme through training and mentoring activities conducted in face-to-face, online, and hybrid modes, consisting of planning, implementation, and evaluation stages. The training materials covered the concept and implementation of deep learning, lesson planning, instructional design and models, learning evaluation, development of innovative technology-based learning media, and reinforcement of microeconomic and macroeconomic content. A total of 78 economics teachers participating in the MGMP of Tasikmalaya City were involved in the program. The results indicate that the training improved teachers’ understanding of deep learning, lesson planning, and assessment strategies that support meaningful learning. Participants’ reflections revealed high motivation and strong relevance of the training materials to their professional duties. This program contributes to strengthening teachers’ readiness to implement deep learning sustainably and supports the improvement of economics learning quality in schools.